Molecular Diversity in Selected Banana Clones (Musa AAA “Cavendish”) : adapted to the Subtropical Environment of Formosa Province (Argentina) - Ermini, José Luis; Tenaglia, Gerardo Carlos; Pratta, Guillermo Raúl (Scientific Research Publishing, 2019)
This study employed Amplified Fragment Length Polymorphism to investigate the genetic variation in local banana plants from farmer’s fields. Forty-four rhizomes (selected from a total of 860 plants for being stable for production) were used as plant material and 6 primer combinations selected in a previous report were used. Polymorphic fragments present in a given genotype were assigned 1 and those absent were assigned 0. The matrix generated was analyzed by univariate and multivariate analysis. A total 540 bands were scored, of which 100% were polymorphic. The number of the pattern duplicated bands was 23 and twenty-one amplicons were exclusive to banana plants collected in the same farmer’s field. Hierarchical clustering and principal coordinates analyses showed differences between genotypes. The cophenetic correlation of the cluster was 0.63 while the 18% of the total molecular variation was explained by the two principal coordinates. These analyses evidence genetic diversity of the crop according to farmer’s field. In agreement to this observation, analysis of molecular variance revealed that 8.9% of the variation was found among farmer populations and 91.1% within farmer populations. In conclusion, introduction of banana into the subtropical zone was associated with a broader genetic variation in order to increase the genetic homeostasis necessary for adapting the crop to the suboptimal environment of Northeastern Argentinean Formosa Province.